Six Sigma success: Looking through authentic leadership and behavioral integrity theoretical lenses - Ajaya K. Swain; Ray Qing Cao; William L. Gardner (Operations Research Perspectives, 2018)
Purpose: The purpose of this research is to broaden the current understanding of the relationship between top leadership characteristics and Six Sigma success. Design/methodology/approach:The research used a cross-sectional survey methodology where 212 companies from six different industries were analyzed to investigate the research question. Findings: This study provides insight into how authentic leaders and leaders with behavioral integrity can facilitate and promote the Six Sigma process in an organization. The key finding is that in order to reap the best benefits of Six Sigma, both qualities in leaders are desired. The study obtains evidence that by staying true to the values they espouse, authentic leaders with high behavioral integrity can foster elevated levels of Six Sigma performance in the workplace. The research model can be applicable in other empirical settings. Research limitations/implications: The current study broadens the existing knowledge about leadership, trust, and performance. While many forms of leadership have been found to motivate employees to perform more effectively through mutual trust, little theory and research has examined the interrelationships among these variables within a Six Sigma context. By identifying authentic leadership and behavioral integrity of leaders as potential enhancers of the effects of top leadership in organizations, our findings represent a departure from prior approaches to understanding the impacts of top leadership on Six Sigma performance. For practitioners, the results of this study further shed light on how leader integrity relates to effective performance and highlights the fact that it is not only important for leaders to remain true to themselves, but they must also walk their talk. The limitations of this study may include the cross-sectional data, specific sample and context in which the proposed relationships were tested that may restrict the generalizability of our findings. Originality/value:The main contribution of this work is the integration and extension of two emerging theories, authentic leadership and behavioral integrity from the leadership literature, to the field of operations management. This study is a timely response to calls from operations management scholars who strongly believe that incorporating theories from organizational behaviour can provide greater insights to practical consequences of implementing operations management practices. To the best of the authors' knowledge, this research is among the first to investigate the relationship between the authenticity and behavioral integrity of a leader and the success factors of a Six Sigma process. The study contributes to the quality management field that has been largely been considered to be lacking on strong theoretical foundations.
Keywords: 330; Authentic leadership; Behavioral integrity; Quality management; Six Sigma; Employee engagement; Factor analysis; Survey research